Cathode active material for non-aqueous electrolyte secondary battery, method for manufacturing cathode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By producing a lithium transition metal composite oxide with controlled composition and surface protection, the structural instability and capacity loss in non-hydrogen secondary batteries are mitigated, enhancing the battery's cycle performance.
Patent Information
- Application Number
- JP2024200555
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-09-17
AI Technical Summary
Lithium transition metal composite oxides with high Ni content used in non-hydrogen secondary batteries experience structural breakdown due to repeated charging and discharging, leading to reduced battery capacity and instability, as well as surface reactions that deteriorate the electrode material.
A method involving the production of a positive electrode active substance using a lithium transition metal composite oxide with controlled composition and surface protection by compounds like CA and SR, combined with specific firing processes to maintain the layered structure and enhance cycle stability.
The solution results in a non-hydrogen secondary battery with improved charging and discharge cycle characteristics by stabilizing the lithium transition metal composite oxide structure, thereby maintaining high battery capacity.
Smart Images

Figure 2025015726000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, lithium transition metal composite oxides with a high Ni content have been attracting attention as positive electrode active materials with high energy density. For example, Patent Document 1 discloses a positive electrode active material for non-aqueous electrolyte secondary batteries, which is made of a lithium transition metal composite oxide represented by the general formula LixNiyCozMmO2 (wherein M is an element selected from Ba, Sr, and B, and 0.9≦x≦1.1, 0.5≦y≦0.95, 0.05≦z≦0.5, and 0.0005≦m≦0.02) and has a BET specific surface area of 0.8 m2 / g or less.
[0003] Patent Document 2 discloses a positive electrode active material for a nonaqueous electrolyte secondary battery, which has an α-NaFeO2 structure, contains one or more transition metal elements selected from the group consisting of Mn, Ni, and Co, and has an alkaline earth metal and W present on the particle surface of a lithium transition metal composite oxide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-100295 A [Patent Document 2] JP 2018-129221 A Summary of the Invention
[0005] When a lithium transition metal composite oxide with a high Ni content is used as the positive electrode active material of a non-aqueous electrolyte secondary battery, the amount of Li extracted during charging is large, and there is a problem that the layered crystal structure is destroyed by repeated charging and discharging, and the capacity decreases. Note that the techniques disclosed in Patent Documents 1 and 2 still have room for improvement in terms of charge and discharge cycle characteristics.
[0006] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure has a layered structure and is represented by the general formula LiaNixMnyMzO2-b (where 0.95 < a < 1.05, 0.7 ≤ x ≤ 0.95, 0 < y ≤ 0.3, 0 ≤ z ≤ 0.3, 0 ≤ b < 0.05, x + y + z = 1, and M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W, and Zn), a lithium transition metal composite oxide, and a compound A containing at least one of Ca and Sr present on the surface or grain boundaries of the primary particles of the lithium transition metal composite oxide. The layered structure includes a Li layer in which Li reversibly enters and exits, and the ratio of metal elements other than Li present in the Li layer is 0.7 mol% or more and 3.0 mol% or less with respect to the total molar amount of metal elements excluding Li in the lithium transition metal composite oxide, and the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (104) plane in the X-ray diffraction pattern by X-ray diffraction is 0.75 ≤ m / n ≤ 1.0.
[0007] The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a step of firing a mixture obtained by dry-mixing a transition metal oxide, a Li compound, and at least one of a Ca compound and a Sr compound at 850°C or lower.
[0008] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery, a negative electrode, and a non-aqueous electrolyte.
[0009] According to the positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure, it is possible to provide a high-capacity non-aqueous electrolyte secondary battery that suppresses a decrease in battery capacity associated with charge and discharge. The positive electrode active material for a non-aqueous electrolyte secondary battery contains a lithium transition metal composite oxide having a high Ni content, which contributes to an improvement in the charge-discharge cycle characteristics of the battery.
Brief Description of the Drawings
[0010] [Figure 1]FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. [Diagram 2] FIG. 2 shows X-ray diffraction patterns of Examples 2 and 3, SrO, and CaO. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The layered structure of the lithium transition metal composite oxide contained in the positive electrode active material contains a transition metal layer containing Ni, a Li layer, and an oxygen layer, and the charge / discharge reaction of the battery progresses as Li ions in the Li layer reversibly enter and exit. When a lithium transition metal composite oxide with a high Ni content is used, many Li ions are extracted from the Li layer during battery charging, causing the layered structure to collapse and leading to a decrease in battery capacity. In addition, lithium transition metal composite oxides with a high Ni content have high activity near the particle surface and tend to have an unstable structure, which makes them prone to the formation of a surface deterioration layer or erosion due to reactions with the electrolyte, leading to a decrease in battery capacity.
[0012] Therefore, the present inventors have conducted intensive research to solve the above problems, and have found that the battery capacity can be increased while maintaining the structure of the lithium transition metal composite oxide by first containing a predetermined amount of Mn, which does not undergo oxidation number change during charging and discharging, in the transition metal layer, and containing a predetermined amount of a metal element other than Li in the Li layer, and further forming a layered structure having a moderate distortion in the plane direction such that the ratio of the half-width m of the (003) plane / the half-width n of the (104) plane in the X-ray diffraction pattern is within a predetermined range. Furthermore, the present inventors have found that the erosion of the structurally deteriorated layer can be suppressed by protecting the surface of the lithium transition metal composite oxide with a compound containing at least one of Ca and Sr. In the case of a lithium transition metal composite oxide with a high Ni content, the reinforcement of the skeleton of the layered structure and the protection of the surface alone cannot provide a sufficient effect, and the charge and discharge cycle characteristics can be specifically improved by applying both of them due to their synergistic effect.
[0013] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body is housed in a cylindrical battery case will be exemplified below, but the electrode body is not limited to the wound type, and may be a laminate type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated one by one with a separator interposed therebetween. In addition, the battery case is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, or the like, or may be a battery case made of a laminate sheet including a metal layer and a resin layer.
[0014] Fig. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in Fig. 1, the nonaqueous electrolyte secondary battery 10 includes an electrode assembly 14, a nonaqueous electrolyte (not shown), and a battery case 15 that accommodates the electrode assembly 14 and the nonaqueous electrolyte. The electrode assembly 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. The battery case 15 includes a cylindrical outer can 16 with a bottom, and a sealing body 17 that closes the opening of the outer can 16.
[0015] The electrode body 14 is composed of a long positive electrode 11, a long negative electrode 12, two long separators 13, a positive electrode tab 20 joined to the positive electrode 11, and a negative electrode tab 21 joined to the negative electrode 12. The negative electrode 12 is formed to have a size slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer in the longitudinal direction and width direction (short direction) than the positive electrode 11. The two separators 13 are formed to have a size at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example.
[0016] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18, 19 disposed above and below the electrode body 14. In the example shown in Fig. 1, a positive electrode tab 20 attached to the positive electrode 11 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and a negative electrode tab 21 attached to the negative electrode 12 passes outside the insulating plate 19 and extends toward the bottom side of the outer can 16. The positive electrode tab 20 is connected to the lower surface of a bottom plate 23 of the sealing body 17 by welding or the like, and a cap 27 of the sealing body 17 electrically connected to the bottom plate 23 serves as a positive electrode terminal. The negative electrode tab 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.
[0017] The exterior can 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the exterior can 16 and the sealing body 17, and the internal space of the battery case 15 is sealed. The exterior can 16 has a grooved portion 22 that supports the sealing body 17 and is formed, for example, by pressing the side portion from the outside. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface.
[0018] The sealing body 17 has a structure in which a bottom plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0019] The positive electrode 11, negative electrode 12, separator 13, and nonaqueous electrolyte that constitute the nonaqueous electrolyte secondary battery 10, and in particular the positive electrode active material contained in the positive electrode mixture layer 31 that constitutes the positive electrode 11, will be described in detail below.
[0020] [Positive electrode] The positive electrode 11 has a positive electrode current collector 30 and a positive electrode composite layer 31 formed on both sides of the positive electrode current collector 30. For the positive electrode current collector 30, a foil of a metal, such as aluminum or an aluminum alloy, that is stable in the potential range of the positive electrode 11, or a film having the metal disposed on the surface layer, can be used. The positive electrode composite layer 31 contains a positive electrode active material, a conductive material, and a binder. The thickness of the positive electrode composite layer 31 is, for example, 10 μm to 150 μm on one side of the positive electrode current collector 30. The positive electrode 11 can be produced by applying a positive electrode slurry containing a positive electrode active material, a conductive material, a binder, and the like to the surface of the positive electrode current collector 30, drying the coating, and then compressing it to form the positive electrode composite layer 31 on both sides of the positive electrode current collector 30.
[0021] Examples of the conductive material contained in the positive electrode mixture layer 31 include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with carboxymethylcellulose (CMC) or a salt thereof, polyethylene oxide (PEO), or the like.
[0022] The positive electrode active material contained in the positive electrode mixture layer 31 includes a lithium transition metal composite oxide having a layered structure, and a compound A containing at least one of Ca and Sr, which is present on the primary particle surfaces, including the secondary particle surfaces, or on the grain boundaries of the lithium transition metal composite oxide.
[0023] Examples of the layered structure of the lithium transition metal composite oxide include a layered structure belonging to the space group R-3m and a layered structure belonging to the space group C2 / m. Among these, a layered structure belonging to the space group R-3m is preferred in terms of high capacity and stability of the crystal structure. The layered structure of the lithium transition metal composite oxide includes a transition metal layer, a Li layer, and an oxygen layer.
[0024] Lithium transition metal composite oxides are generally represented by the formula Li a Ni x Mn y Mz O 2-b (wherein 0.95 < a < 1.05, 0.7 ≤ x ≤ 0.95, 0 < y ≤ 0.3, 0 ≤ z ≤ 0.3, 0 ≤ b < 0.05, x + y + z = 1, and M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W, and Zn). In addition, the positive electrode active material may contain a lithium transition metal composite oxide other than that represented by the above general formula, or other compounds, as long as the object of the present disclosure is not impaired. The molar fraction of the metal elements contained in the lithium transition metal composite oxide can be measured by an inductively coupled plasma optical emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0025] a, which represents the ratio of Li in the lithium transition metal composite oxide, satisfies 0.95 ≤ a < 1.05, and preferably satisfies 0.97 ≤ a ≤ 1.03. When a is less than 0.95, the battery capacity may decrease as compared with the case where a satisfies the above range. When a is 1.05 or more, it may lead to a deterioration in charge-discharge cycle characteristics as compared with the case where a satisfies the above range.
[0026] x, which represents the ratio of Ni to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, satisfies 0.7 ≤ x ≤ 0.95, and preferably satisfies 0.8 ≤ x ≤ 0.95. By setting x to 0.7 or more, a high-capacity battery can be obtained. In addition, when x is 0.8 or more, the effect of improving cycle characteristics due to the stabilization of the structure of the lithium transition metal composite oxide is easily obtained. When x exceeds 0.95, a sufficient amount of Mn and M cannot be contained, so the layered structure of the lithium transition metal composite oxide becomes unstable.
[0027] The content y representing the content of Mn with respect to the total molar number of metal elements excluding Li in the lithium transition metal composite oxide preferably satisfies 0 < y ≦ 0.3, and more preferably satisfies 0.01 ≦ y ≦ 0.15. Since the oxidation number of Mn does not change even during charge and discharge, it is considered that the structure of the transition metal layer is stabilized by being contained in the transition metal layer. On the other hand, when y exceeds 0.3, the content of Ni decreases and the battery capacity decreases. Mn may be uniformly dispersed, for example, within the layered structure of the lithium transition metal composite oxide, or may be present in a part within the layered structure.
[0028] M (where M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W, and Zn) is an optional component. The content z representing the content of M with respect to the total molar number of metal elements excluding Li in the lithium transition metal composite oxide preferably satisfies 0 ≦ z ≦ 0.3.
[0029] The lithium transition metal composite oxide is, for example, particles having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means the particle diameter at which the cumulative frequency in the volume-based particle size distribution becomes 50% from the smaller particle diameter side, and is also called the median diameter. The particle size distribution of the lithium transition metal composite oxide can be measured using a laser diffraction type particle size distribution measuring device (for example, MT3000II manufactured by Microtrac Bell Co., Ltd.) with water as the dispersion medium.
[0030] The lithium transition metal composite oxide is, for example, secondary particles formed by aggregation of a plurality of primary particles. The particle diameter of the primary particles constituting the secondary particles is, for example, 0.05 μm to 1 μm. The particle diameter of the primary particles is measured as the diameter of the circumscribed circle in the particle image observed by a scanning electron microscope (SEM).
[0031] Compound A is present on the surface or grain boundary of the primary particles of the lithium transition metal composite oxide. This can suppress the generation and erosion of a structurally deteriorated layer on the surface of the lithium transition metal composite oxide due to a reaction with an electrolyte or the like. Here, the surface of the primary particles includes the surface of the secondary particles. The grain boundary of the primary particles is the interface between the primary particles. The presence of compound A on the surface or grain boundary of the primary particles means a state in which compound A is in contact with the surface or grain boundary of the primary particles, or a state in which compound A is within a range of 10 nm or less from the surface or grain boundary of the primary particles. Compound A may be, for example, uniformly dispersed over the entire surface and interface of the lithium transition metal composite oxide, or may be present only in a part of it.
[0032] Compound A contains at least one of Ca and Sr. Compound A may contain a Ca compound or a Sr compound. Examples of Ca compounds include CaO, Ca(OH)2, and CaCO3. Examples of Sr compounds include SrO, Sr(OH)2, and SrCO3.
[0033] The total amount of Ca and Sr in compound A may be 1 mol % or less based on the total molar amount of metal elements other than Li in the lithium transition metal composite oxide, thereby making it possible to further improve the charge-discharge cycle characteristics.
[0034] The layered structure of the lithium transition metal composite oxide includes a Li layer in which Li reversibly enters and exits, and the ratio of metal elements other than Li present in the Li layer is 0.7 mol% or more and 3.0 mol% or less with respect to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide. If the ratio of metal elements other than Li in the Li layer is less than 0.7 mol%, the stability of the layered structure decreases when Li ions in the Li layer are extracted, causing the structure to break and leading to a decrease in battery capacity. If the ratio of metal elements other than Li in the Li layer exceeds 3.0 mol%, the diffusivity of Li ions in the Li layer decreases, causing a decrease in battery capacity and an increase in the reaction resistance of the battery. The metal element present in the Li layer is mainly Ni, but may contain other metal elements.
[0035] The ratio of metal elements other than Li in the Li layer can be obtained from the Rietveld analysis results of the X-ray diffraction pattern obtained by X-ray diffraction measurement of the positive electrode active material. For the Rietveld analysis of the X-ray diffraction pattern, for example, Rietveld analysis software PDXL2 (Rigaku Corporation) can be used.
[0036] The X-ray diffraction pattern is obtained by a powder X-ray diffraction method using a powder X-ray diffractometer (manufactured by Rigaku Corporation, product name "RINT-TTR", radiation source Cu-Kα) under the following conditions. Measurement range: 15-120° Scan speed: 4° / min Analysis range: 30-120° Background: B-spline Profile function: Split pseudo-Voigt function Constraint condition: Li(3a)+Ni(3a)=1 Ni(3a) + Ni(3b) = α (α is the Ni content in each) ICSD No.:98-009-4814 The positive electrode active material preferably has a crystallite size s calculated from the half-width n of the diffraction peak of the (104) plane in the X-ray diffraction pattern by the Scherrer equation of 400 Å≦s≦800 Å. If the crystallite size s of the lithium transition metal composite oxide is smaller than 400 Å, the crystallinity may decrease, leading to a decrease in the battery capacity. If the crystallite size s of the lithium transition metal composite oxide exceeds 800 Å, the diffusivity of Li may decrease, leading to a decrease in the output characteristics of the battery. The Scherrer equation is expressed by the following formula.
[0037] s=Kλ / Bcosθ In the above formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.
[0038] The positive electrode active material has a ratio m / n of the half-width m of the diffraction peak of the (003) plane to the half-width n of the diffraction peak of the (104) plane in the X-ray diffraction pattern by the X-ray diffraction, which is 0.75≦m / n≦1.0. If the ratio is within this range, the layered structure can be in a state of moderate distortion in the plane direction, so that a battery with high capacity and improved charge / discharge cycle characteristics can be obtained. If the ratio m / n is less than 0.75, the layered structure is too distorted and becomes brittle. If the ratio m / n is more than 1.0, the battery capacity decreases.
[0039] It is preferable that the X-ray diffraction pattern of the positive electrode active material by the X-ray diffraction measurement does not include peaks derived from CaO and SrO. If CaO and SrO are contained to such an extent that they are detectable by the X-ray diffraction measurement, a decrease in battery capacity may occur.
[0040] Next, an example of a method for producing a positive electrode active material containing a lithium transition metal composite oxide and compound A will be described.
[0041] The method for producing a positive electrode active material includes, for example, a first step of obtaining a transition metal oxide containing Ni, Mn, and an arbitrary metal element, a second step of mixing the transition metal oxide obtained in the first step with a Li compound to obtain a mixture, and a third step of firing the mixture.
[0042] In the first step, for example, while stirring a solution of a metal salt containing Ni, Mn, and an arbitrary metal element (Co, Al, Nb, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (co-precipitating) a transition metal hydroxide containing Ni, Mn, and the arbitrary metal element, and the transition metal hydroxide is calcined to obtain a transition metal oxide containing Ni, Mn, and the arbitrary metal element. The calcination temperature is not particularly limited, but is, for example, in the range of 300°C to 600°C.
[0043] In the second step, the transition metal oxide obtained in the first step is dry-mixed with a Li compound and at least one of a Ca compound and a Sr compound to obtain a mixture. Examples of Li compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of Ca compounds include Ca(OH)2, CaO, CaCO3, CaSO4, and Ca(NO3)2. Examples of Sr compounds include Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, and Sr(NO3)2. The mixing ratio of the transition metal oxide obtained in the first step and the Li compound is preferably, for example, such that the molar ratio of metal elements other than Li to Li is in the range of 1:0.98 to 1:1.1, in order to easily adjust each of the parameters to the ranges specified above. In addition, the mixing ratio of the transition metal oxide obtained in the first step and the Ca compound or Sr compound is preferably set such that, for example, the molar ratio of metal elements other than Li:Ca and Sr is in the range of 1:0.0003 to 1:0.03, in order to facilitate adjustment of each of the above parameters within the ranges specified above. In the second step, when mixing the transition metal oxide obtained in the first step, the Li compound, and the Ca compound or Sr compound, other metal raw materials may be added as necessary. The other metal raw materials are oxides containing metal elements other than the metal elements constituting the transition metal oxide obtained in the first step, etc.
[0044] In the third step, the mixture obtained in the second step is fired at 850°C or less for a predetermined time to obtain the positive electrode active material according to the present embodiment. If fired at a temperature exceeding 850°C, the compound A containing at least one of Ca and Sr may aggregate in a specific portion, and sufficient effects may not be obtained. The firing of the mixture in the third step includes a multi-stage firing process including a first firing process in which the mixture is fired in a firing furnace under oxygen flow at a first heating rate to a first set temperature of 450°C to 680°C, and a second firing process in which the fired product obtained by the first firing process is fired in a firing furnace under oxygen flow at a second heating rate to a second set temperature of more than 680°C to 850°C. Here, the first heating rate is in the range of 1.5°C / min to 5.5°C / min, and the second heating rate is slower than the first heating rate, in the range of 0.1°C / min to 3.5°C / min. The first heating rate and the second heating rate may be set in a plurality of rates for each temperature range, so long as they are within the ranges specified above. The holding time of the first set temperature in the first firing step is preferably 5 hours or less, more preferably 3 hours or less, in terms of adjusting each of the parameters of the lithium transition metal composite oxide to the ranges specified above. The holding time of the first set temperature is the time during which the first set temperature is maintained after the first set temperature is reached. The holding time of the second set temperature in the second firing step is preferably 1 hour to 10 hours, more preferably 1 hour to 5 hours, in terms of adjusting each of the parameters of the lithium transition metal composite oxide to the ranges specified above. The holding time of the second set temperature is the time during which the second set temperature is maintained after the second set temperature is reached. When firing the mixture, in terms of adjusting each of the parameters to the ranges specified above, the firing is performed, for example, in an oxygen stream with an oxygen concentration of 60% or more, and the flow rate of the oxygen stream is set to 10 cm / s of the firing furnace. 3 The flow rate can be in the range of 0.2 mL / min to 4 mL / min per kg of mixture and 0.3 L / min or more per kg of mixture.
[0045] The molar fraction of the metal element contained in the positive electrode active material obtained above was measured by inductively coupled plasma (ICP) emission spectrometry and was expressed by the general formula Li a Ni x Mn y M z Ca α Sr β O2-b (wherein, 0.95 < a < 1.05, 0.7 ≤ x ≤ 0.95, 0 < y ≤ 0.3, 0 ≤ z ≤ 0.3, α + β > 0, 0 ≤ b < 0.05, x + y + z = 1, and M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W, and Zn). Note that Ca and Sr are contained in Compound A present on the surface of the lithium transition metal composite oxide.
[0046] [Negative electrode] The negative electrode 12 includes a negative electrode current collector 40 and a negative electrode composite layer 41 formed on both surfaces of the negative electrode current collector 40. As the negative electrode current collector 40, a foil of a metal stable within the potential range of the negative electrode 12 such as copper or a copper alloy, or a film having such a metal disposed on the surface layer can be used. The negative electrode composite layer 41 contains a negative electrode active material and a binder. The thickness of the negative electrode composite layer 41 is, for example, 10 μm to 150 μm on one side of the negative electrode current collector 40. The negative electrode 12 can be manufactured by applying a negative electrode composite slurry containing a negative electrode active material, a binder, etc. to the surface of the negative electrode current collector 40, drying the coating film, and then rolling to form the negative electrode composite layer 41 on both surfaces of the negative electrode current collector 40.
[0047] The negative electrode active material contained in the negative electrode composite layer 41 is not particularly limited as long as it can reversibly occlude and release lithium ions, and generally, carbon materials such as graphite are used. The graphite may be any of natural graphite such as flake graphite, massive graphite, and earthy graphite, artificial massive graphite, and artificial graphite such as graphitized mesophase carbon microbeads. Further, as the negative electrode active material, metals that alloy with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. may be used. Also, those provided with a carbon coating may be used. For example, a Si-containing compound represented by SiO x (0.5 ≤ x ≤ 1.6), or Li 2y SiO (2+y) A Si-containing compound in which fine particles of Si are dispersed in a lithium silicate phase represented by (0 < y < 2) may be used in combination with graphite.
[0048] The binder contained in the negative electrode mixture layer 41 may be a fluorine-containing resin such as PTFE or PVdF, PAN, polyimide, acrylic resin, polyolefin, or the like, as in the case of the positive electrode 11, but is preferably styrene-butadiene rubber (SBR). The negative electrode mixture layer 41 may also contain CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like.
[0049] [Separator] For example, a porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have a single-layer structure or a laminated structure. In addition, a highly heat-resistant resin layer such as an aramid resin, or a filler layer containing an inorganic compound filler may be provided on the surface of the separator 13.
[0050] [Non-aqueous electrolyte] The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these can be used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine. Examples of the halogen-substituted product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).
[0051] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).
[0052] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, and the like. and chain ethers such as ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0053] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiMnCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borates such as Li2B4O7, Li(B(C2O4)F2), LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2){l, m are integers of 0 or more}, and imide salts such as these can be mentioned. As the lithium salt, these may be used alone or in combination of plural kinds. Among these, from the viewpoints of ionic conductivity, electrochemical stability, etc., it is preferable to use LiPF6. The concentration of the lithium salt is, for example, 0.8 mol to 1.8 mol per 1 L of the non-aqueous solvent. Further, vinylene carbonate or a propane sultone-based additive may be added.
Example
[0054] Hereinafter, the present disclosure will be further described by way of examples and comparative examples, but the present disclosure is not limited to the following examples.
[0055] [Preparation of Cathode Active Material] <Example 1> General formula Ni 0.82 Mn 0.03 Co 0.15The transition metal oxide was mixed with Sr(OH)2 and Ca(OH)2 so that the contents of Sr and Ca were 1.0 mol% and 0.1 mol%, respectively, relative to the total amount of Ni, Mn, and Co of the transition metal oxide represented by O2, and lithium hydroxide monohydrate (LiOH·H2O) was further mixed so that the molar ratio of Li to the total amount of Ni, Mn, Co, Sr, and Ca was 1:1.03. The mixture was fired under an oxygen stream with an oxygen concentration of 95% (flow rate of 5 L / min per 1 kg of the mixture) at a heating rate of 2°C / min from room temperature to 650°C, and then fired at a heating rate of 1°C / min from 650°C to 800°C. Impurities were removed by washing the fired product with water to obtain the positive electrode active material of Example 1. The composition of the positive electrode active material of Example 1 was analyzed by ICP-AES, and the results showed that Li 0.99 Ni 0.82 Mn 0.03 Co 0.15 Sr 0.01 Ca 0.001 O2. In addition, the positive electrode active material of Example 1 was subjected to X-ray diffraction measurement. The ratio of metal elements other than Li present in the Li layer to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide was 0.87 mol%. The ratio m / n of the half-width m of the diffraction peak of the (003) plane to the half-width n of the diffraction peak of the (104) plane in the X-ray diffraction pattern by X-ray diffraction was 0.978.
[0056] [Preparation of positive electrode] The above positive electrode active material was mixed in a ratio of 95 parts by mass, 3 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder, and this was mixed with N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Next, the slurry was applied to a positive electrode current collector made of aluminum foil with a thickness of 15 μm, and after drying the coating film, the coating film was rolled with a rolling roller and cut into a predetermined electrode size to obtain a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode core. In addition, an exposed portion in which the surface of the positive electrode core was exposed was provided in a part of the positive electrode.
[0057] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0058] [Preparation of test cell] An aluminum lead was attached to the exposed part of the positive electrode, and a nickel lead was attached to the lithium metal foil as the negative electrode, and the positive electrode and the negative electrode were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was housed in an exterior body made of an aluminum laminate sheet, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a test cell.
[0059] [Evaluation of capacity retention rate] The test cell was subjected to the following cycle test. The discharge capacity at the first cycle and the discharge capacity at the 30th cycle of the cycle test were obtained, and the capacity retention rate was calculated by the following formula.
[0060] Capacity retention rate (%) = (30th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100 <Cycle test> The test cell was charged at a constant current of 0.2 It in a temperature environment of 25°C until the battery voltage reached 4.3 V, and then charged at a constant voltage until the current value reached 1 / 100 It at 4.3 V. Then, the test cell was discharged at a constant current of 0.2 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 30 times.
[0061] <Examples 2 and 4> Test cells were prepared in the same manner as in Example 1, except that the raw materials, raw material compounding ratio, total amount of metal elements other than Li to Li molar ratio were changed to 1:1.05, and the second-stage baking temperature was changed to 750°C to synthesize the positive electrode active material, and then the test cells were evaluated.
[0062] <Example 3> Test cells were prepared and evaluated in the same manner as in Example 4, except that the raw material composition ratio was changed and the positive electrode active material was synthesized under an oxygen flow with an oxygen concentration of 95% (flow rate of 10 L / min per 1 kg of mixture).
[0063] <Example 5> Test cells were prepared in the same manner as in Example 2, except for the raw materials used, the raw material compounding ratio, and the fact that the positive electrode active material was synthesized by firing from room temperature to 650°C at a heating rate of 5°C / min, and then firing from 650°C to 750°C at a heating rate of 3°C / min, and then evaluating the test cells.
[0064] <Examples 6 to 8> Test cells were produced in the same manner as in Example 1, except that the raw materials used, the raw material blending ratio, and the second-stage baking temperature were changed to 730° C. to synthesize the positive electrode active material, and then the test cells were evaluated.
[0065] <Comparative Example 1> Test cells were produced in the same manner as in Example 1, except that the raw material blend ratio was changed to synthesize the positive electrode active material, and the test cells were evaluated.
[0066] <Comparative Example 2> Test cells were produced and evaluated in the same manner as in Example 2, except that the raw materials and the raw material blending ratios used were changed to synthesize the positive electrode active materials.
[0067] <Comparative Example 3> Test cells were prepared in the same manner as in Example 2, except that the raw material composition ratio, the molar ratio of the total amount of metal elements other than Li to Li was changed to 1:0.95, and the second-stage firing temperature was changed to 850°C to synthesize the positive electrode active material, and then the test cells were evaluated.
[0068] <Comparative Example 4> Test cells were prepared and evaluated in the same manner as in Example 2, except that the raw materials used, the raw material mixing ratio, and the positive electrode active material were synthesized under an oxygen flow with an oxygen concentration of 95% (flow rate of 0.1 L / min per 1 kg of mixture).
[0069] <Comparative Example 5> Test cells were produced in the same manner as in Example 6, except that the raw materials and the raw material blending ratios used were changed to synthesize the positive electrode active materials, and the test cells were evaluated.
[0070] <Comparative Example 6> Test cells were produced in the same manner as in Example 1, except that the raw materials used, the raw material blending ratio, and the second-stage baking temperature were changed to 730° C. to synthesize the positive electrode active material, and then the test cells were evaluated.
[0071] <Comparative Example 7> Test cells were prepared in the same manner as in Example 7, except that the raw material compounding ratio and the molar ratio of the total amount of metal elements other than Li to Li were changed to 1:1.1 to synthesize the positive electrode active material, and then the test cells were evaluated.
[0072] The capacity retention rates of the examples and comparative examples are shown in Tables 1 to 3. The evaluation results of the capacity retention rates shown in Tables 1 to 3 are shown relatively to the capacity retention rates of the test cells of Comparative Examples 1, 2, and 5, which are set to 100%. Tables 1 to 3 also show the ratio m / n of the half-width m of the diffraction peak of the (003) plane to the half-width n of the diffraction peak of the (104) plane in the X-ray diffraction pattern by X-ray diffraction, and the ratio of metal elements other than Li present in the Li layer to the total number of moles of metal elements other than Li.
[0073] [Table 1]
[0074] [Table 2]
[0075] [Table 3] As shown in Tables 1 to 3, Examples 1 to 8 had higher capacity retention rates than Comparative Examples 1 to 7. In addition, in the X-ray diffraction patterns of all the Examples, there were no peaks derived from SrO or CaO. As an example, the X-ray diffraction patterns of Examples 2 and 3 and SrO and CaO are shown in FIG. [Explanation of symbols]
[0076] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Battery case 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive tab 21 Negative electrode tab 22 Grooved part 23 Bottom plate 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket 30 Positive electrode current collector 31 Positive electrode mixture layer 40 Negative electrode current collector 41 Negative electrode composite layer
Claims
1. A compound having a layered structure, the general formula Li a Ni x Mn y M z O 2-b (wherein 0.95<a<1.05, 0.7≦x≦0.95, 0<y≦0.3, 0≦z≦0.3, 0≦b<0.05, x+y+z=1, and M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W, and Zn), A compound A containing at least one of Ca and Sr, which is present on the surface or grain boundary of a primary particle of the lithium transition metal composite oxide, the layered structure includes a Li layer into which Li reversibly enters and exits, and a ratio of metal elements other than Li present in the Li layer is 0.7 mol % or more and 3.0 mol % or less with respect to a total molar amount of metal elements other than Li in the lithium transition metal composite oxide, A positive electrode active material for a non-aqueous electrolyte secondary battery, wherein the ratio m / n of the half-width m of a diffraction peak of a (003) plane to the half-width n of a diffraction peak of a (104) plane in an X-ray diffraction pattern by X-ray diffraction satisfies 0.75≦m / n≦1.
0.
2. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the total amount of Ca and Sr in said compound A is 1 mol % or less with respect to the total molar amount of metal elements other than Li in said lithium transition metal composite oxide.
3. 3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the crystallite size s calculated from the half-width n of the diffraction peak of the (104) plane in an X-ray diffraction pattern by Scherrer's formula is in the range of 400 Å≦s≦800 Å.
4. 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein no peaks derived from CaO or SrO are present in an X-ray diffraction pattern obtained by X-ray diffraction measurement.
5. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, comprising the steps of: A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: baking a mixture obtained by dry-mixing a transition metal oxide, a Li compound, and at least one of a Ca compound and a Sr compound at 850° C. or lower.
6. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, a negative electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Manufacture of nonaqueous solvent secondary battery
JP2000195514A
Positive active material for lithium secondary battery, its manufacturing method, and lithium secondary battery
JP2009032467A
Sulfur-doped lithium transition metal oxides
JP2010535699A
Positive electrode active material for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell
WO2019131234A1
Positive electrode material for lithium secondary battery and manufacturing method thereof
JP2003100295A